2017
DOI: 10.1177/0886260517744192
|View full text |Cite
|
Sign up to set email alerts
|

The Association Among Parental Bonding, Depression, Social Aggression, and Criminal Assault: Are There Gender Differences Between Male and Female Youth Offenders?

Abstract: This research examined similarities and differences in gender regarding social aggression, criminal assault, depression, and familial factors. The participants were 251 youth offenders (158 males) who were arrested and incarcerated in a juvenile facility. The measures consisted of self-reported acts of social aggression, simple and aggravated assault, subtypes of depression, and self-reports on parental care and control. Our data demonstrate the importance of including gender, types of aggression/assault, subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Although previous research has shown that negative parental behaviours tend to affect to boys and girls in a different way, to the best of our knowledge, it is the first study that reports these results applied to cyberbullying. In this sense, recent studies have reported that negative parenting (especially those parental practices related to the management of misbehaviour such as high control or punishment) increases the likelihood of girls to develop externalizing and aggressive behaviours [55,56] and that girls seem to be more affected by negative parental practices which favour that they feel more hurt and less loved than boys [57]. This evidence helps to understand our findings which suggest that negative parenting in girls is associated not only to the lack of skills to cope cyber-victimization situations, but also to an important maladjustment which also leads them to bully others through ICT.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous research has shown that negative parental behaviours tend to affect to boys and girls in a different way, to the best of our knowledge, it is the first study that reports these results applied to cyberbullying. In this sense, recent studies have reported that negative parenting (especially those parental practices related to the management of misbehaviour such as high control or punishment) increases the likelihood of girls to develop externalizing and aggressive behaviours [55,56] and that girls seem to be more affected by negative parental practices which favour that they feel more hurt and less loved than boys [57]. This evidence helps to understand our findings which suggest that negative parenting in girls is associated not only to the lack of skills to cope cyber-victimization situations, but also to an important maladjustment which also leads them to bully others through ICT.…”
Section: Discussionmentioning
confidence: 99%
“…Past findings have shown that physical aggression and verbal aggression are separate constructs (e.g., J. Tisak, Maynard, & Tisak, 2002), in addition to larceny, weapon offenses, and illicit versus minor drug use (e.g., Tisak & Tisak, 2016). Although less research has focused on the differences in school, home, or social violations, there are data suggesting that children from a young age do not evaluate home and school conventions in the same manner (e.g., Tisak et al, 2000).…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…In addition, past research (reviewed in Tisak, 1995) shows that it is important to categorize different types of moral violations. That is, even though violations such as vandalism, physical aggression, verbal aggression, and larceny affect the welfare of others, they may not be evaluated in the same way as previous research suggests (Tisak & Tisak, 2016). Moreover, it may also be important that violations within the social conventional domains be categorized as those involving school versus those involving home misbehaviors (Tisak, Crane-Ross, Tisak, & Maynard, 2000).…”
mentioning
confidence: 97%
“…Both males and females presented with high numbers of aggressive and externalizing symptoms at pre-assessment and the number of participants were sufficiently high to reliably identify a number of classes in both groups (Wurpts and Geiser 2014). Several studies have suggested that emotional closeness and quality of the caregiver-child relationship may play a greater role in females' internalizing and delinquent behavior relative to males (Hart et al 2007;Lewis et al 2015;Tisak et al 2017). In this regard, it may be important to include additional variables such as relationship quality or internalizing symptoms when analyzing female behavior, rather than relying on conduct behaviors alone.…”
Section: Discussionmentioning
confidence: 98%